Improving access to sexual and reproductive health services among adolescent women in Zimbabwe - M Mhlanga; A Mangombe; J J Karumazondo; T Yohannes (Bioscientifica, 2024)
Background: Unplanned pregnancies increased among adolescents in Zimbabwe, resulting in unsafe abortions, sexual and gender-based violence, and forced marriages. Access to Sexual and Reproductive Health and Rights (SRHR) has been scanty among pregnant adolescents and adolescent mothers owing to negative social norms, stigma and discrimination. This project specifically targeted pregnant adolescents and adolescent mothers through a differentiated and targeted care approach to improve uptake and sexual and reproductive health outcomes. Methods: Target-specific peer support groups for pregnant adolescents and adolescent mothers were established in Epworth district of Zimbabwe. The Champions of Change, a peer-based approach, was used to facilitate comprehensive sexuality education. Mentors were adolescent mothers trained on how to use a tailor-made manual to facilitate sessions. Two health centers, namely Epworth Clinic and Overspill Clinic, were purposively selected to participate in this study. A total of 60 participants were recruited into this study, 30 from each clinic. Knowledge and attitude were measured using a semi-structured questionnaire administered before and after the intervention. A scorecard was used to assess friendliness and quality of service provision. A Chi-square test of association was used to determine the significance of the change in outcomes. Results: A significant improvement in knowledge of SRHR, attitudes, and healthcare-seeking behaviors was noted. There was a significant improvement in attitudes and friendliness in service provision. Access to services significantly increased with improvements in relationships and trust. Conclusion: A targeted and differentiated care approach increases the uptake of services and health outcomes among adolescent women by addressing their unique needs and circumstances.